Electrostimulation to Increase Peroneal Muscle Strength in Pediatric Patients With Postsurgical Clubfoot - Guadalupe Morales-Osorio; Joel Lomeli-Gonzalez; Noemi Isela Hernandez-Valadez; Elena Arellano Saldana; Maria Luz Arenas-Sordo (Mazandaran University of Medical Sciences, 2016)
Background: Idiopathic congenital clubfoot is a deformity with various components. Its treatment can be conservative and or surgical in order to eliminate the deformity and to obtain a pain-free foot allowing for adequate mobility. Objectives: Our objective was to evaluate whether neuromuscular electrostimulation is useful for improving peroneal muscle strength in post-operative congenital clubfoot in children. Patients and Methods: An experimental, prospective, longitudinal, and comparative study was carried out on 10 patients with congenital clubfoot in the experimental group, and on 10 for historical controls. Initial and post-treatment clinical evaluations were conducted on patients in both groups. Surface electromyography (SEMG) was used for the experimental group; each patient received 30 sessions of treatment with neuromuscular electrostimulation in order to obtain muscular contraction. Results: In both groups, there were more males with the average age or 5.5 years (ranging from 3 to 8 years of age). Peroneal muscular strength evaluated through the Daniels and Worthingham's test increased post-treatment only in the experimental group, and comparing these results to those of the historical group, a significance level of P = 0.001 was obtained. The motor unit potential amplitude in the SEMG increased in the experimental group with a significance level of P < 0.05. Conclusions: Neuromuscular electrostimulation can be used to increase muscle strength, and it is a safe and painless treatment.